Estimates of vertical velocity by numerical and analytical methods -A comparison - RAO, K. V.; RAJAMANI, S. (MAUSAM, 1972)
Numerical computations with the complete w-equation for quasi-geostrophic adiabatic motion have been made for comparison with earlier computations with a simplified form of w-equation. Also an attempt has been made to check the magnitudes of vertical velocity computed by the simplified w-equation, with the values obtained from Kuo’s analytical expression for w. The extent to which there is agreement has been discussed.